2003
DOI: 10.3201/eid0903.020545
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in Sri Lanka: Splendid Isolation

Abstract: Rabies virus exists in dogs on Sri Lanka as a single, minimally divergent lineage only distantly related to other rabies virus lineages in Asia. Stable, geographically isolated virus populations are susceptible to local extinction. A fully implemented rabies-control campaign could make Sri Lanka the first Asian country in >30 years to become free of rabies virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 7 publications
2
17
0
1
Order By: Relevance
“…There are previous reports of a variant of Rabies virus in southern India that is related to Sri Lankan lineage [1,4,9,10]. Although the robust bootstrap resampling values and their phylogenetic distance from other clusters identified them as a distinct group the above studies altogether identified only a few isolates but speculated the prevalence of this variant.…”
mentioning
confidence: 65%
“…There are previous reports of a variant of Rabies virus in southern India that is related to Sri Lankan lineage [1,4,9,10]. Although the robust bootstrap resampling values and their phylogenetic distance from other clusters identified them as a distinct group the above studies altogether identified only a few isolates but speculated the prevalence of this variant.…”
mentioning
confidence: 65%
“…This included viruses from South-east Asia, namely Myanmar, Thailand, Laos, Cambodia and Vietnam (Ito et al , 1999; Yamagata et al , 2007), China (Meng et al , 2007; Zhang et al , 2006) and also from Indonesia and The Philippines (Nishizono et al , 2002). Finally, the Indian subcontinent clade of RABV was distributed only within southern India and Sri Lanka (Arai et al , 2001; Nanayakkara et al , 2003). This clade is particularly notable because it occupies a basal position on the non-flying mammal part of the RABV phylogeny based on N sequences (bootstrap support of 73 %), suggesting that it was the first of this group to diverge.…”
Section: Resultsmentioning
confidence: 99%
“…In Sri Lanka, dogs are the most important animals responsible for the transmission of the rabies virus [38][39]. The REA requires that all dogs over six weeks of age be vaccinated [36].…”
Section: Discussionmentioning
confidence: 99%